2013
DOI: 10.1080/13803395.2012.760536
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in children and adolescents with restrictive-type anorexia nervosa: An in-depth investigation with NEPSY–II

Abstract: Several studies have investigated the neuropsychological functioning of patients with anorexia nervosa restrictive type (AN-r), but results are conflicting. Here we compared the neuropsychological profile of 23 female children and adolescents with AN-r and of 46 typical controls (aged 9-16 years) using the second edition of the NEPSY (a Developmental Neuropsychology Assessment) neuropsychological battery. AN-r patients presented subtle cognitive flexibility impairments in audiomotor responses (p = .033). Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 65 publications
4
28
0
Order By: Relevance
“…1 The differences in the TAVEC reported by Oltra-Cucarella et al (2014) (F 1,38 = 5.213, p = .028) became nonsignificant when the Stroop-W (F 1,37 = .697, p = .409), the Stroop-C (F 1,38 = 2.386, p = .131), the Stroop-CW (F 1,37 = 1.276, p = .266) and the SDMT (F 1,37 = .046, p = .831) were introduced independently and as a group (F 1,34 = .187, p = .668). The differences between patients with and without depression reported by Calderoni et al (2013) (F 1, 19 = 5.2, p = .034) became nonsignificant when EF were partialled out (F 1, 18 = 4.179, p = .056), although a trend for significance was found. Both results would support our hypothesis.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…1 The differences in the TAVEC reported by Oltra-Cucarella et al (2014) (F 1,38 = 5.213, p = .028) became nonsignificant when the Stroop-W (F 1,37 = .697, p = .409), the Stroop-C (F 1,38 = 2.386, p = .131), the Stroop-CW (F 1,37 = 1.276, p = .266) and the SDMT (F 1,37 = .046, p = .831) were introduced independently and as a group (F 1,34 = .187, p = .668). The differences between patients with and without depression reported by Calderoni et al (2013) (F 1, 19 = 5.2, p = .034) became nonsignificant when EF were partialled out (F 1, 18 = 4.179, p = .056), although a trend for significance was found. Both results would support our hypothesis.…”
Section: Discussionmentioning
confidence: 46%
“…Matthias & Kent (1998) found delayed recall impairments even when EF was significantly better in participants with AN. Calderoni et al (2013) found no difference in EF or in verbal memory between the AN and the healthy control groups, but reported that patients with mood disorders scored significantly higher than expected from the normative group and that patients without an associated mood disorder on the recall score. On the other hand, if EF affects verbal memory then controlling for their effects as covariates would have turned results non-significant.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Second, the role of depression on neuropsychological performances remains unclear although a clarification of this issue would be much needed (Giel et al, 2012) also given its frequent comorbidity with AN (O'Brien and Vincent, 2003). In fact, some studies failed to find an effect of depressive comorbidity on neuropsychological aspects (Sarrar et al, 2011;Calderoni et al, 2013;Sato et al, 2013) but the majority of the studies did not take comorbidity into account.…”
Section: Introductionmentioning
confidence: 94%
“…The majority of recent research on adolescent patients is in line with this finding, showing no deficits in cognitive flexibility at all or only subtle impairments (e.g. Bühren et al ., ; Calderoni et al ., ; Fitzpatrick, Darcy, Colborn, Guforf, & Lock, ; Shott et al ., ). In a previous study, we also found only subtle cognitive flexibility impairments in a group of adolescent patients with AN compared with a CG (Sarrar et al ., ).…”
Section: Introductionmentioning
confidence: 99%